Yahoo Web Search

1. Sort by

1. k - 3 > 1 or k - 3 < -1?

Solving the first inequality gives you k - 3 > 1 add 3 to both sides k - 3 + 3 > 1 + 3 k > 4 ...that vertical line. We used a dotted or dashed line through k = 4 to indicate that that is not part of the solution. If we used...

1 Answers · Education & Reference · 17/05/2008

k/5 + 1 = k/3 + 5 15[k/5 + 1 = k/3 + 5] {multiplied entire equation by LCD, 15, to clear fractions} 15(k/5) + 15(1) = 15(k/3) + 15(5) {multiplied each term by 15} 3k + 15...

3 Answers · Education & Reference · 04/10/2010

3. Simplify -kr^9q^2 divided by k^3rq^5?

= - k • (r^9) • (q^2)   ⁄   [ (k^3) • r • (q^5)  ]     ... subtract exponents of similar terms when dividing  = - ( k^- 2 ) • (r^8) • (q^- 3)  = - (r^8)   ⁄   [ (k^2) • (q^3...

1 Answers · Education & Reference · 26/07/2013

1) The K in JK Rowling stands for Kathleen. When... name, Kathleen. So J (Joanne) K (Kathleen) R (Rowling) 2) C - Roddy ...

3 Answers · Education & Reference · 13/11/2012

5. What is the equation of K?

If line K is perpendicular, that means that its slope is a negative reciporical...

1 Answers · Education & Reference · 30/10/2012

6. if the equation of the line tangent to the curve f(x) = kx + 8 / k +x at x = -2 is y = x +4, find the value of?

assuming k is a constant f(x) = (kx + 8) / (k + x) f '(x) = [(k + x) * k - (kx + 8... ... [using the quotient rule] f '(x) = [k² + kx - kx - 8] / (k + x)² f '(x) = (k² - 8) / (k + x)² when x = -2, f '...

2 Answers · Education & Reference · 20/11/2011

7. show that the equation ( k -1)x^2+2x-(k-3)=0 has real roots for all values of k?

0 = (k –1)x² + 2x – (k – 3)               discriminant = ...  +  4(k –1)(k –3) The expression 4 • (k –1) • (k – 3) has a MINIMUM at the vertex, which is...

2 Answers · Education & Reference · 27/05/2013

8. can someone help me find the function K described by K (x) =6x find?

K(x) = 6x K(-2) = 6(-2) = -12 K(5) = 6(5) = 30 K(35) = 6(35) = 210

1 Answers · Education & Reference · 27/02/2008

9. Find the range of values of K satisfying the inequality?

k^2 + 9k + 14 > 0 (k + 2)(k + 7) > 0 k > -2 or k < -7 in the interval notation : (-∞, -7) U (-2, ∞)

2 Answers · Education & Reference · 11/10/2013

10. Please solve the equation: 9(k-1)=-4k^2?

9(k-1)=-4k^2 4*k^2 + 9*K - 9 = 0 use the quadratic formula: http://www.mathsisfun.com/algebra.../quadratic-formula.gif with a = 4, b = 9, c = -9 and, of course, x = k and you get: k = {-9 +|- squareroot[9^2 - 4*16*(-9)]}/(2*4) = {-9 +|- squareroot...

3 Answers · Education & Reference · 30/11/2012